Use of Drugs and Treatment Cost in Acute Watery Diarrhoea of Under-2 Children Attending a Tertiary Hospital of Bogra (Journal of Medicine, 2014)
A cross-sectional study was conducted in Mohammad Ali hospital (MAH) of Bogra from Bangladesh to evaluate the hand washing and exclusive breast feeding (EBF) practice and to explore the rational use of anti-diarrhoeal therapy in Acute Watery Diarrhea (AWD) and expenditure of the family in treatment. A total of 660 under-2 children attending at MAH with the complaints of AWD were selected for the study. The mean age (mean±SD) of the attended child was 11.75±5.16 months. About 80% of the respondents (mothers of under-2 child) were below SSC level in terms of educational status while about 9% were illiterate. About 85% of the respondent seek treatment from non-registered practitioners (NRP) while registered doctors contributed only among 12% which was found statistically significant in comparison to their family income (p